Attention Allocation to Physically Separate Task and Situation Displays in a Command and Control Setting. (December 2020) - Golan, H.; Parush, A.; Jaffe, E.
Using a simulated Emergency Medical Services (EMS) dispatch center during multi-casualty incident management, this study explored whether the presence of a separate situation display in a Command and Control (C2) setting might require attention at the expense of attending an individual task display, and how it influenced performance and situational awareness. Overall, participants always attended the task display more than the situation display. However, the situation display drew attention at the expense of attending less the task display. The presence of the situation display was related to improved performance and better situational awareness (SA), particularly in the projection level of the SA, which could account also for the better decision-making performance. Participants may have developed an attention allocation strategy to effectively utilize the information of the situation display and execute their tasks on the task display.